High grade upper tract urothelial carcinoma in an ectopic kidney: case report and review of literature - Siddhant Kumar; Padmaraj Hegde; Ankit Agarwal; K. R. Surag; Siddalingeshwara Chandragouda Doddamani (African Journal of Urology)
Abstract Case A 67-year-old male with hematuria and diagnosed to have a left iliac fossa malrotated ectopic kidney with enhancing renal pelvic mass; which on histopathological examination was noted to be high grade UTUC- pT3N1. Conclusion This is the first documented high grade UTUC case of an ectopic kidney in literature. The treatment of this disease can be challenging due in part to its aberrant vascular morphology and due to its location.